Interferences of HbA1c analysis in Hospital Universiti Sains Malaysia – 3 years study - Noorazliyana Shafii,; Noor Azlin Azraini Che Soh,; Tuan Salwani Tuan Ismail,; Julia Omar,; Wan Norlina Wan Azman,; Aniza Mat Jelani,; Wan Nor Fazila Hafizan Wan Nik,; Ibrahim Ismail,; Nur Karyatee Kassim,; Hanim Afzan Ibrahim,; Najib Majdi Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Haemoglobin A1c (HbA1c) is used to monitor glycaemic control and predict diabetic complications. Measurement of HbA1c can be interfered by haemoglobin (Hb) variant and other Hb derivatives include carbamylated Hb and elevated labile A1c. This study is to determine the percentages and type of interferences during HbA1c analysis and the percentages of nonreportable HbA1c results. This is a cross-sectional study using retrospective data of HbA1c. The HbA1c is measured on Biorad D10 using the ion-exchange high-performance liquid chromatography method. The data were analyzed using descriptive statistics. A total of 26,560 patients were included. The result showed the presence of interferences of 2269 (8.56%). The most common causes of the interferences were the Hb variant (8.48%) followed by carbamylated Hb and labile A1c (0.03% each). The non-reportable HbA1c results were 0.46% with the Hb variant contributed most of the causes. By knowing the presence of interferences particularly the Hb variant, the HbA1c results hopefully are interpreted with caution and correct management can be given to the patients.